2022
DOI: 10.3390/ijms232214357
|View full text |Cite
|
Sign up to set email alerts
|

The Mucus Binding Factor Is Not Necessary for Lacticaseibacillus rhamnosus CRL1505 to Exert Its Immunomodulatory Activities in Local and Distal Mucosal Sites

Abstract: Both viable and non-viable orally administered Lacticaseibacillus rhamnosus CRL1505 modulate immunity in local (intestine) and distal (respiratory) mucosal sites. So, intestinal adhesion and colonization are not necessary for this probiotic strain to exert its immunomodulatory effects. In this work, a mucus-binding factor knockout CRL1505 strain (ΔmbfCRL1505) was obtained and the lack of binding ability to both intestinal epithelial cells and mucin was demonstrated in vitro. In addition, two sets of in vivo ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…CRL1050 Mbf is highly homologous to Mbf of L. rhamnosus GG [ 21 ]. Recently, we showed that the Mbf protein of L. rhamnosus CRL1505 contributed to adhesion to the extracellular matrix and to porcine intestinal cells [ 16 ]. These previous works clearly demonstrated the role of the Mbf protein in adhesion of lactobacilli to the intestinal mucosa, although its involvement in the adhesion to the respiratory tract was not investigated before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CRL1050 Mbf is highly homologous to Mbf of L. rhamnosus GG [ 21 ]. Recently, we showed that the Mbf protein of L. rhamnosus CRL1505 contributed to adhesion to the extracellular matrix and to porcine intestinal cells [ 16 ]. These previous works clearly demonstrated the role of the Mbf protein in adhesion of lactobacilli to the intestinal mucosa, although its involvement in the adhesion to the respiratory tract was not investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…L. rhamnosus CRL1505 and Lactiplantibacillus plantarum CRL1506 were obtained from the CERELA culture collection (Tucumán, Argentina). L. rhamnosus Δmbf CRL1505 is a mucus-binding protein knock-out that was constructed and phenotypically checked by Tomotsune et al [ 16 ]. The L. plantarum MPL16 and L. salivarius FFIG58 strains were obtained from the Food and Feed Immunology Group–Tohoku University culture collection (Sendai, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation